Ferroptosis Induction in Pentylenetetrazole Kindling and Pilocarpine-Induced Epileptic Seizures in Mice - Mao, Xiao-Yuan; Zhou, Hong-Hao; Jin, Wei-Lin (Frontiers in Neuroscience, 2019)
Epilepsy is a serious neurological disorder and characterized by recurrent and unprovoked seizures. A critical pathological factor in the seizure genesis is neuronal loss. Until now, apart from the known regulatory cell death pathways, the newest one is ferroptosis, a newly discovered type of cell death with the features of iron accumulation and excessive production of lipid reactive oxygen species (ROS). In our present work, it was illustrated that ferroptosis occurred in murine models of pentylenetetrazole (PTZ) kindling and pilocarpine (Pilo)-induced seizures. In both of these two seizure models, treatment with ferroptosis inhibitor ferrostatin-1 (Fer-1) efficiently alleviated seizures. This was through elevated levels of glutathione peroxidase 4 (GPX4) and glutathione (GSH) as well as inhibitions of lipid degradation product including 4-hydroxynonenal (4-HNE) and malonaldehyde (MDA), iron accumulation and PTGS2 mRNA in hippocampus. It is concluded that ferroptosis is involved in the seizure genesis in PTZ- and Pilo-treated mice, and suppression of ferroptosis mitigates PTZ kindling and Pilo-induced seizures in mice.